シングルNi-Tiロータリーファイルによる湾曲根管形成の評価 - Mika TANAKA; 武藤 徳子; Kaori SHIMOJIMA; Naohiro TOMINAGA; 石井 信之 (The Japanese Journal of Conservative Dentistry, 2014)
Purpose: The purpose of this study was to determine the shaping ability of the reciprocating nickel-titanium (Ni-Ti) single-file system (Reciproc: VDW, Germany; WaveOne: Dentsply Maillefer, Switzerland) and rotary multiple system (ProTaper: Dentsply Maillefer) by measuring canal transportation. Methods: One hundred and twenty-six J-shaped canals in resin blocks were used in this experiment. The J-shaped canals had three different apical curvatures (10 (n=42), 20 (n=42), 30 (n=42) degrees) and were randomly classified into 6 groups: Reciproc R25, WaveOne Primary, ProTaper SX-S1-S2-F1-F2, Reciproc R40, WaveOne Large, and ProTaper SX-S1-S2-F1-F2-F3-F4. Each group consisted of a model of 10 (n=7), 20 (n=7), and 30 (n=7) degrees. Canal transportation was assessed by comparing pre-instrumentation and post-instrumentation images under an Olympus SZX16 with digital camera DP71, and the superimposed images were analyzed by WinRoof. Results: After adjusting for the level and canal wall side, the mean transportation was not significantly different between Reciproc R25, WaveOne Primary, and ProTaper SX-S1-S2-F1-F2 in the final preparation size of ISO#25. A significantly lower deviation was found with Reciproc R40 and WaveOne Large for 10 degrees curvature, by ProTaper SX-S1-S2-F1-F2-F3-F4 for 20 degrees, and by Reciproc R40 for 30 degrees in the final preparation size of ISO#40. Conclusions: These findings suggest that the reciprocating Ni-Ti single-file Reciproc and WaveOne are suitable systems for preparing curved canals, the same as the rotary multiple system ProTaper. 目的 : 本研究は, 往復運動により駆動するNi-TiシングルファイルReciprocとWaveOneの湾曲根管形成時の根管壁変位量を, 複数本で根管形成を行うProTaperと比較検討することを目的とした.  材料と方法 : 実験には, 根尖部湾曲が10, 20, 30度の湾曲角度を有するJ型エポキシレジン製透明湾曲根管模型各42本, 合計126本を使用し根管形成実験群を6群 (各群n=7×3) に分類した. 各実験群は最終根管形成号数がISO#25のReciproc R25, WaveOne Primary, および対照群のProTaper SX-S1-S2-F1-F2と最終根管形成号数がISO#40のReciproc R40, WaveOne Large, および対照群のProTaper SX-S1-S2-F1-F2-F3-F4に分類した. 各実験群の切削効率の測定は, 根管形成前後の透明湾曲根管模型を重ね合わせ, その差異を実体顕微鏡Olympus SZX16およびデジタルカメラDP71を用いて撮影し, さらに計測用ソフトWinRoofを使用して計測を行い, 根管壁変位量とした.  結果 : 切削効率を測定した結果, 最終拡大号数#25のReciproc R25, WaveOne Primary, および対照群のProTaperでは, すべてのファイルにおいて有意差が認められなかった. 一方, 最終拡大号数#40では湾曲10度の根管ではReciproc R40, WaveOne Large, 湾曲20度の根管ではProTaper, 湾曲30度の根管ではReciproc R40が, 最も根管壁変位量が小さく根管形態を保持していることが示された.  結論 : Ni-TiシングルファイルReciprocとWaveOneによる根管形成は, 複数本で形成するProTaperと同様に正確な根管形成が可能であることが示された.